Study guide with student's solutions manual for Statistics for management and economics - Keller, Gerald. (Duxbury Press, 1998)
What is statics? Graphical descriptive techniques. Art and science of graphical presentations. Numerical descriptive techniques. data collection and sampling. Probability and discrete probability distributions. Continuous probability distribution...